Estudo comparativo de caso de duas instituições tecnológicas em relação a gestão institucional de projetos de P&D. - Skrobot, Luiz Claudio (2005)
Studies comparing two technological institutes in Mercosul -The Industrial Technologic Institute, in Argentina, and the Technological Research Institute, in Brazil - focus on management projects in research and Development, in institutional level. Through the literature, it is identify, areas and subjects that allow the analyses of institutional management R&D projects (IMRDP). The history of the two institutes was study to identify the similarity and the differences of them. The field research is composed by an interview which was framed through literature subjects and documents in the following topics: general vision and IMRDP operations in the institutes; institutional management; process effectives results; people´s communication involved with projects and the institution; experiences acquired in the institutions. Of all interviews, one quarter was directed to high management, one quarter to functional gerency and two quarter to project managers. The discussion results, thanks to the methodology and schedule, determined that institutions did not have IMRDP, although both institutions considered the importance of its implementation. It was clear that the IMRDP structure, in any institution, have to consider the institutional culture, history, staff, structure and market, even though there are similar subjects and areas between the two institutions.